Effect of the rectus femoris kinesio-taping on male athletes during the stop-jump task post-fatigue - Chang, Y. A.; Huang, C. (ISBS Proceedings Archive (Michigan), 2019)
This study aimed to investigate the biomechanics of the stop-jump task under the effect of Kinesio-taping (KT) applied on rectus femoris before and after fast-induced fatigue on male athletes. Nine male college athletes served as the subject. Two force plates and ten high-speed cameras were synchronized to capture the stop-jump tasks. The results showed that the jumping height decreased, the vertical ground reaction force (GRF) and the peak proximal tibia anterior shear force increased, and the time to peak vertical GRF was earlier after intervened fatigue in the non-taping group. We also found that the peak proximal tibia anterior shear force did not increase after fatigue when following the application of KT. We recommend that KT is used to intense exercises or competition with repeated jumping.